3 - Teaching Styles of Educators in Higher Education in Eritrea: Teacher-centred or Student-centred? - Abdella, Ali Suleman; Fataar, Aslam (Journal of Higher Education in Africa, 2022)
To meet the demands of twenty-first-century educational needs in Eritrea, the country required the education sector to replace passive learning and didactic pedagogy with interactive learning and student-centred pedagogy. In line with reform initiatives, teacher education programmes aim to prepare student teachers to increase their prospective students’ participation in the classroom. The purpose of the study on which this article is based was to find out the extent to which educators used student-centred strategies in realising the reform initiatives. The methodology adopted was survey research design. A questionnaire based on the Principles of Adult Learning Scale was used to generate data from sixty-one educators at two teacher education institutions, namely the College of Education of the Eritrea Institute of Technology and Asmara Community College of Education. While student-centred teaching has been advocated, the findings indicate that teacher-centred teaching dominates instructional settings. Moreover, the study examined the relationship between teaching styles and the demographic features of educators using an analysis of variance. No significant differences were found between teaching styles and various demographic aspects of the teacher educators.